Kajian Literatur Metode Pada Sistem Pendukung Keputusan Penentuan Dosen Berkinerja Terbaik - Nidya Kusumawardhany (Jurnal Ticom: Technology of Information and Communication, 2022)
Abstract— The purpose of this study is to describe a literature review on the determination or selection of lecturers with the best performance. The research method used is a qualitative research method with a literature review approach. The research steps begin with determining the topic, collecting journals with the chosen topic, analyzing the selected journals and making a review. The journals used as sources of research data were taken from 2015 to 2022 with the keywords "Best Lecturer", "Determination Method" and "Best Lecturer Selection". Processing of data sourced from 26 (twenty six) journals begins with grouping based on Research Objectives, Research Results, Methods and Criteria used. With so many decision support system methods, the results are the top 3 (three) methods, namely the first Simple Additive Weighting (SAW) method of 34.6%, the second is the Analytical Hierarchy Process (AHP) of 23.1% and the third is the Weighted Product (WP) of 15.4%. And for the most widely used criteria in previous studies, the 3 (three) highest order was firstly C2-Teaching (Teaching Length, Academic Rank) amounting to 57.7%, secondly C1-Research (Number of Publications (reputable)) amounting to 53.8%, and thirdly C8 -Pedagogic aspects (learning, teaching materials, learning media) amounted to 53.8%. The decision support system is one of the most widely used methods in the process of determining or selecting the best performing lecturers. The methods used can be combined to obtain optimal and objective results.